Miasma as Earthquake Impact Depicted in Ambon Manuscript: A Disaster Semiotic Perspective - Suryanto, Ardiansyah Bagus; Mohammad Rofiqi; Bahauddin; Sulanam; Mu’jizah; Azhar Ibrahim; Priscila Fitriasih Limbong (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2024)
This study aims to explore the concept of miasma and the spiritual implications of earthquakes as depicted in the Naskah Cerita Gempa (The Story of Earthquake) manuscript found in Ambon, “The Story of Earthquake” is a manuscript from the collection of Husain Hatuwe. It is cataloged in both the Ambon Manuscript Catalog and the Religious Catalog of the Makassar Research and Development Center, under the Ministry of Religious Affairs of the Republic of Indonesia. The manuscript has been digitized through a collaborative effort between the Pernaskahan Nusantara Foundation and the Faculty of Cultural Sciences at the University of Indonesia, in partnership with the Endangered Archives Programme (EAP) of the British Library. The digitized version of “The Story of Earthquake” manuscript can be accessed online via the EAP British Library’s website using the code EAP276/7/10. This study employs a textual analysis adopting Han-Liang Chang’s disaster semiotics methodology which categorizes disasters into three phases: natural events, interpretations and effects. The findings of this study reveal that natural events, in the form of weather changes associated with miasma, have a significant impact on all forms of life, including animals, plants and humans. These changes lead to damage and death, prompting individuals to seek protection. This research underscores the profound spiritual and physical effects of natural disasters as interpreted through the lens of the Naskah Cerita Gempa manuscript.